Women's work in public relations - Bridgen, Elizabeth; Williams, Sarah (Emerald Publishing Limited, 2024)
The experience of women's everyday lives in public relations roles across the world is under-recorded and under-explored. While the body of knowledge which explores public relations and corporate communications is growing, research that seeks to understand the working lives of women in promotional cultures is still limited. This collection prioritises women's experiences and histories to understand more about public relations practices and the daily lives of women who carry out this work. Demonstrating the breadth and range of feminist writing on women's work, chapters step away from management-based accounts of public relations towards a space where marginalised voices and the lived experiences of women at all stages in their career are foregrounded. Discussing working lives in Brazil, Spain, Bosnia, Turkey, the UK and beyond, authors consider in rich detail female roles, experiences and paradoxes. Reconceptualising human experience through a holistic feminist approach, Women's Work in Public Relations takes us behind the scenes to connect with women navigating the problems and contradictions of everyday working life.